A Review of the Potential Factors Influencing Myopia Progression in Children Using Orthokeratology. Issue 6 (November 2016) - Yang, Xiao; Li, Zhouyue; Zeng, Junwen
Abstract : Abstract: Myopia has become a worldwide public health issue. Recent studies have consistently reported that orthokeratology (Ortho-K) significantly inhibits the progression of myopia by slowing the elongation of axial length. It has been hypothesized that this effect results from the induction of peripheral myopic defocus, which is a result of the effects of the Ortho-K lenses on the midperipheral corneal topography. Previous studies have investigated the relationship between predicting factors and the inhibitory effect of Ortho-K for slowing childhood myopic progression and found some meaningful results; however, some of the findings are controversial. To enhance the understanding of the underlying mechanism of Ortho-K in slowing childhood myopic progression, the factors affecting this process were reviewed.